2007
DOI: 10.1021/jm061010z
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Selective Nonpeptidic Inhibitors of Procollagen C-Proteinase

Abstract: 6-Cyclohexyl-N-hydroxy-3-(1,2,4-oxadiazol-5-yl)hexanamides were previously disclosed as inhibitors of procollagen C-proteinase (PCP) culminating in the identification of amide 1. Our objective was to discover a second inhibitor that would have improved affinity for PCP and to optimize properties for transepidermal delivery (TED) to intact skin. Further investigation of this template identified a number of potent PCP inhibitors (IC50 values of 2-6 nM) with improved TED flux. Sulfonamide 56 had excellent PCP enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 21 publications
3
59
2
Order By: Relevance
“…The inhibitor used was 5-((R)-4-cyclohexyl-1-hydroxycarbamoylmethyl-butyl)-[1,2,4]oxadiazole-3-carboxylic acid amide, corresponding to compound 1 in Ref. 23. A titration experiment using the same inhibitor showed that it binds in a 1:1 ratio with BMP-1, in keeping with the enzymatic active site titration data (Fig.…”
Section: Characterization Of Bmp-1 By Nmrsupporting
confidence: 58%
“…The inhibitor used was 5-((R)-4-cyclohexyl-1-hydroxycarbamoylmethyl-butyl)-[1,2,4]oxadiazole-3-carboxylic acid amide, corresponding to compound 1 in Ref. 23. A titration experiment using the same inhibitor showed that it binds in a 1:1 ratio with BMP-1, in keeping with the enzymatic active site titration data (Fig.…”
Section: Characterization Of Bmp-1 By Nmrsupporting
confidence: 58%
“…Based on this observation, we postulate that such a reduction could offer an additional mechanism for reducing formation of fibrillar deposits. The idea of blocking BMP-1 to limit fibrosis was suggested by others, and a number of inhibitors of BMP-1 have been developed and tested as potential inhibitors of fibrosis (36). At the same time, however, it has been demonstrated that, in addition to procollagen I, BMP-1 cleaves other substrates and that its activity is critical for a number of processes not related to fibrosis (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that direct modification of these biochemical signals results in reduced adult skin scarring. [87][88][89][90][91][92] For example, neutralization of TGF-b1/2 and/or addition of TGF-b3, 88 downregulation of connexin 43 (Cx43) protein levels, 89 and exogenous application of angiotensin peptides 87 have all been shown to reduce scar formation in adult skin. However, these studies are validated primarily in animal models.…”
Section: Mechanomodulation and Emerging Mechanotherapiesmentioning
confidence: 99%